THE USE OF A SITUATIONAL PRESENTATION IN TEACHING ENGLISH GRAMMAR - CRISTINA PIELMUŞ (Studia Universitatis Babes-Bolyai, 2020)
ABSTRACT. The purpose of this paper is to highlight one of the lesson frameworks that can be used in an English language class in order to teach grammar, while also integrating into the lesson the practice of language skills. A situational presentation teaching method is used in English language teaching contexts and is also known as a Presentation-Practice-Production. The aim of such a lesson is to introduce to students a scenario that will enable them to discover the target language, which they will later on practise in the lesson. Thus, this teaching format will give the students the opportunity to acquire new grammar knowledge that will be further practised along the lesson in restricted and freer practice activities. In the freer practice the students will be able to integrate the new grammar into activities designed to stimulate the practice of productive skills, such as speaking, while interacting with their peers. The article will include self-made samples of tasks and resources used in an English language class focused on teaching grammar and a clear description of the lesson stages for the full comprehension of this lesson framework, while pointing out the benefits and some of the drawbacks of such a method in the realm of English language teaching.